A case of Wiskott-Aldrich syndrome with de novo mutation at exon 4 - Doğu, Figen; Ariga, Tadashi; Ikincioğullari, Aydan; Bozdoğan, Günseli; Aytekin, Caner; Metin, Ayşe; Babacan, Emel (The Turkish Journal of Pediatrics, 2006)
Wiskott-Aldrich syndrome (WAS) is an X-linked disorder characterized by thrombocytopenia, eczema and immunodeficiency. Clinical features of the disease are highly varied; therefore, the diagnosis is sometimes difficult, especially in solitary cases or cases with milder forms of the disease. However, the identification of the WASP gene has made possible a definite WAS diagnosis for these cases. In this report, we present a 26-month-old boy who had received several ineffective treatments for chronic immune thrombocytopenic purpura. He was then suspected to have WAS because of the early onset of thrombocytopenia and small platelets. The diagnosis became definite with the detection of a de novo mutation at exon 4 of the WASP gene, Arg138Pro, through mutation analysis.